How Does Indonesia Carry out Learning Recovery to Overcome Learning Loss During The Covid-19 Pandemic? - Anju Nofarof Hasudungan; Mariano dos Santos (Education & Learning, 2026)
This study aims to describe the learning recovery carried out by the Indonesian government to overcome learning loss during the COVID-19 pandemic. The Ministry of Education, Culture, Research, and Technology of the Republic of Indonesia conducts learning recovery in the following ways: 1) Issue emergency curriculum and internet quota subsidies; 2) Flexibility and rebudgeting of the School Operational Assistance Fund Program (BOS); 3) Eliminating school exams and postponing the Minimum Competency Assessment (AKM); 4) Develop Rumah Belajar and Guru Belajar & Berbagi platforms; 5) Implementing Limited Face-to-Face Learning, and a prototype curriculum that will be implemented. This study used a qualitative descriptive study with 206 students as research subjects from ten schools in Riau Province selected by purposive sampling technique. Data were collected through interviews, test results, literature study, document analysis, and observation. Data analysis was carried out by adopting the interactive model of Miles and Huberman. The results show that the Indonesian government is far better than other developing countries in learning recovery. In the future, the Indonesian government needs to speed up vaccinations for teachers and students so that limited face-to-face learning can still be carried out, improve digital infrastructure and ensure prototype curriculum is fit for purpose.